Identification of the key exosomal lncRNAs/mRNAs in the serum during distraction osteogenesis - Tao Zhang; Weidong Jiang; Fengchun Liao; Peiqi Zhu; Lina Guo; Zhenchen Zhao; Yan Liu; Xuanping Huang; Nuo Zhou (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Distraction osteogenesis (DO), a kind of bone regenerative process, is not only extremely effective, but the osteogenesis rate is far beyond ordinary bone fracture (BF) healing. Exosomes (Exo) are thought to play a part in bone regeneration and healing as key players in cell-to-cell contact. The object of this work was to determine whether exosomes derived from DO and BF serum could stimulate the Osteogenic Differentiation in these two processes, and if so, which genes could be involved. Methods The osteogenesis in DO-gap or BF-gap was evaluated using radiographic analysis and histological analysis. On the 14th postoperative day, DO-Exos and BF-Exos were isolated and cocultured with the jaw of bone marrow mesenchymal stem cells (JBMMSCs). Proliferation, migration and osteogenic differentiation of JBMMSCs were ascertained, after which exosomes RNA-seq was performed to identify the relevant gene. Results Radiographic and histological analyses manifested that osteogenesis was remarkably accelerated in DO-gap in comparison with BF-gap. Both of the two types of Exos were taken up by JBMMSCs, and their migration and osteogenic differentiation were also seen to improve. However, the proliferation showed no significant difference. Finally, exosome RNA-seq revealed that the lncRNA MSTRG.532277.1 and the mRNA F-box and leucine-rich repeat protein 14(FBXL14) may play a key role in DO. Conclusions Our findings suggest that exosomes from serum exert a critical effect on the rapid osteogenesis in DO. This promoting effect might have relevance with the co-expression of MSTRG.532277.1 and FBXL14. On the whole, these findings provide new insights into bone regeneration, thereby outlining possible therapeutic targets for clinical intervention.